Effects of a Solar Flare on the Martian Hot O Corona and Photochemical Escape. Issue 14 (25th July 2018) - Lee, Yuni; Dong, Chuanfei; Pawlowski, Dave; Thiemann, Edward; Tenishev, Valeriy; Mahaffy, Paul; Benna, Mehdi; Combi, Michael; Bougher, Stephen; Eparvier, Frank
Abstract: We examine for the first time the flare‐induced effects on the Martian hot O corona. The rapid ionospheric response to the increase in the soft X‐ray flux (~800%) facilitates more hot O production at altitudes below the main ionospheric peak, but almost all of these atoms are thermalized before escape. In response to the increase in the extreme ultraviolet (EUV) flux (~170%), the overall upper ionospheric and thermospheric densities are enhanced, and the peak thermospheric responses are found ~1.5 hr later. The photochemical escape rate is predicted to increase by ~20% with the increases in the soft X‐ray and EUV fluxes but decrease rapidly by ~13% about 2.5 hr later before recovering the preflare level. Since escaping hot O atoms are mostly produced at high altitudes where ionization by the EUV flux is the greatest, the main contributor to the 20% increase in escape rate is the enhancement in the EUV flux. Plain Language Summary: We present for the first time the flare‐induced effects on the loss of neutral O atoms from the atmosphere of Mars. This study found that the main contributor to the sudden increase in the O loss rate is the increase in the solar extreme ultraviolet flux during the flare event, which induces more energetic O atoms at high altitudes where they can easily escape to space. Our investigation will contribute to the earlier works on the atmospheric loss from Mars by providing additional knowledge about the variability of the neutral escape. Key Points: We examine for the first time the flare‐induced effects on the Martian hot O corona and photochemical escape The photochemical escape rate increases by ~20% in the case that describes the peak response time of the ionosphere during the flare event We found that the main contributor to the increase in escape rate is the enhancement in the EUV flux